Answer:
whats your question im confused
Step-by-step explanation:
Answer:
(3)(x+7)(x-1)
Step-by-step explanation:
3x^2+18x-21
Let's start by taking 3 out of the equation.
3(x^2+6x-7)
Now, when we factor, we need to find two numbers that add up to 6 and multiply to -7.
The numbers would be 7 and -1.
So the factored form of this would be:
(3)(x+7)(x-1)
Answer:
20 years old
Step-by-step explanation:
Joe = J
Sydney = S
J = 5 + S
J + S = 45
Substitute
5 + S + S = 45
Add
5 + 2S = 45
Subtract 5 from both sides of the equation
2S = 40
Divide both sides of the equation by 2
S = 20
Sydney is 20 years old
Hope this helps :)
So with this, I will be using the substitution method. With the first equation, substitute (y+3) into the x variable and solve for y:
Next, now that we have the value of y, substitute it into either equation to solve for x:
<u>And this is how you get your final answer (5,2).</u>
Answer:
D
Step-by-step explanation:
We know that vector addition is scalar addition.
Given vectors are u = <-3.5, -1.5> and v = <-1.25, 2.25>
2v = < -2.5, 4.5>
2v - u = < -2.5, 4.5> - <-3.5, -1.5> = < -2.5 - (-3.5) , 4.5 -(-1.5) >
2v-u = < 1 , 6 >
This vector is basically i + 6j which is drawn in option D